Comparative Effectiveness of Intracerebroventricular, Intrathecal, and Intranasal Routes of AAV9 Vector Administration for Genetic Therapy of Neurologic Disease in Murine Mucopolysaccharidosis Type I - Belur, Lalitha R.; Romero, Megan; Lee, Junggu; Podetz-Pedersen, Kelly M.; Nan, Zhenhong; Riedl, Maureen S.; Vulchanova, Lucy; Kitto, Kelley F.; Fairbanks, Carolyn A.; Kozarsky, Karen F.; Orchard, Paul J.; Frey, William H.; et al. (Frontiers in Molecular Neuroscience, 2021)
Mucopolysaccharidosis type I (MPS I) is an inherited metabolic disorder caused by a deficiency of the lysosomal enzyme alpha-L-iduronidase (IDUA). The two current treatments for MPS I (hematopoietic stem cell transplantation and enzyme replacement therapy) are ineffective in addressing neurologic disease, in part due to the inability of lysosomal enzyme to cross the blood brain barrier. With a goal to more effectively treat neurologic disease, we have investigated the effectiveness of AAV-mediated IDUA gene delivery to the brain using several different routes of administration. Animals were treated by either direct intracerebroventricular (ICV) injection, by intrathecal (IT) infusion into the cerebrospinal fluid, or by intranasal (IN) instillation of AAV9-IDUA vector. AAV9-IDUA was administered to IDUA-deficient mice that were either immunosuppressed with cyclophosphamide, or immunotolerized at birth by weekly injections of human iduronidase. In animals treated by ICV or IT administration, levels of IDUA enzyme ranged from 3-fold to 1000-fold that of wild type levels in all parts of the microdissected brain. In animals administered vector intranasally, enzyme levels were 100-fold that of wild type in the olfactory bulb, but enzyme expression was close to wild type levels in other parts of the brain. Glycosaminoglycan levels were reduced to normal in ICV and IT treated mice, and in IN treated mice they were normalized in the olfactory bulb, or reduced in other parts of the brain. Immunohistochemical analysis showed extensive IDUA expression in all parts of the brain of ICV treated mice, while IT treated animals showed transduction that was primarily restricted to the hind brain with some sporadic labeling seen in the mid- and fore brain. At six months of age, animals were tested for spatial navigation, memory, and neurocognitive function in the Barnes maze; all treated animals were indistinguishable from normal heterozygous control animals, while untreated IDUA deficient animals exhibited significant learning and spatial navigation deficits. We conclude that intrathecal and intranasal routes are acceptable and alternate routes of administration respectively, of AAV vector delivery to the brain with effective IDUA expression, while all three routes of administration prevent the emergence of neurocognitive deficiency in a mouse MPS I model.